PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PROBLEM BASED LEARNING MATERI ARITMATIKA SOSIAL - Devi Novita; Sugeng Riyadi; Ahde Fitri (Pendidikan Matematika | STKIP YM Bangko, 2022)
The goal of this research is to develop LKPD on based problem-based learning on the subject of social arithmetic for class VII SMP Negeri Satu Atap 20 Merangin which are valid, practical, and effective. This form of research is known as Research and Development (R&D) and it follows a 4-D model has four stages, namely define, design, development, and disseminate. The validation sheet completed by five validators demonstrates validity. Practicality can be viewed from the practicality questionnaire and interviews with students. While learning activities and student learning outcomes are used to determine the effectiveness. The results viewed that the average score of the material expert validation results was 4.55, linguist validation was 4.50, and media expert validation was 5.00. The overall validation score was 4.68 has a very valid category. Student response questionnaires gained a percentage of 80.46% has a practical category. Students' learning activities get an average of 75.11% has a active category and the percentage of classical learning outcomes is 82.35% has a effective category. Based on the research results, LKPD on based problem-based learning are valid, practical, and effective